Multimodality in english classes as a foreing language to teenagers (2022)
By way of conclusion, after the research approached, the following can be concluded. - The learning mechanisms, especially in other languages, are complex for students, and the educational structure must work to strengthen didactic tools to guarantee the motivation to learn other languages. - The current digitalization allows students to choose to watch and listen to videos or read posts in other languages, which will guarantee effective learning. - English as a universal language requires practice and perseverance, which means that if the dynamic is accepted by the students, they will make a significant effort to write posts in a better way or to express themselves better orally, using more techniques due to the deployment of these practices.